Concept Demonstrator for MeerKAT Operation from 14.5 to 20 GHz - Mundia, Sitwala (Department of Electrical Engineering, 2020)
In this thesis, a proof of concept receiver system operating from 14.5 to 20 GHz for the MeerKAT Radio Telescope is presented. MeerKAT is a 64 element telescope antenna array consisting of offset-fed Gregorian reflector antennas with a 13.5 m main reflector and 3.8 m sub-reflector. Currently, the MeerKAT is planned to operate up to 14.5 GHz. However, the reflector surface accuracy of 0.6 mm RMS achieved for the MeerKAT potentially allows it to operate at much higher frequencies. The system design consists of a feed horn antenna and front-end down conversion receiver ready for integration with back-end digital signal processing. The antenna design was carried out using electromagnetic simulation software and system level simulation software was used for the front-end receiver. A single polarization wide-axially corrugated horn with low side-lobes and cross-polarization has been designed for the proof of concept with a predicted aperture efficiency of 60% including surface accuracy loss when illuminating the MeerKAT reflector. The measured results for the antenna show a return loss better than 15 dB in the operational band and boresight gain of 12 dB. The measured E- and H-plane cross-polarization for the antenna is lower than -40 dB. The measured edge taper at the halfsubtended angle of the sub-reflector is between -11.8 dB and -13.2 dB. The front-end receiver was designed to use a single down-conversion stage to a 4.5 GHz IF with an instantaneous bandwidth of 2.5 GHz to be bandpass sampled at 6 Giga-samples per second (GSPS). The receiver was designed using off-the-shelf connectorized modules and custom designed microstrip filters for image rejection and anti-aliasing. Laboratory measurements of the receiver show a maximum gain of 76 dB, 40 dB image rejection and 27 dB spurious free dynamic range (SFDR). The simulated noise figure of the system using the measured noise figure of the LNA is 1.74 dB. The measured gain flatness of the receiver is ±7 dB due to poor performance of one of the amplifier modules used in the system.